The Qiyas Paradigm in Ushul al-Nahwi: A Comparative Study ‎of the Basrah and Kufah Schools ‎ - Febriyani, Gita; Asrina (Journal of Practice Learning and Educational Development, 2026)
Qiyas (analogical reasoning) is one of the foundational principles for formulating rules in the science of syntax (Arabic grammar). To date, the application of Qiyas as a basis for establishing grammatical rules has been marked by numerous differences and disputes between the two major schools: Basrah and Kufah. The objective of this article is to conduct an in-depth analysis of Qiyas as a foundation of grammatical science. The research employs a qualitative method with a library research approach. This involves a series of activities related to gathering data from written sources, such as Ibn Al-Anbari's Al-Insaf Fi Masa'il Al-Khilaf as the core analytical material, supplemented by secondary sources from classical and contemporary literature on the comparison of the Basrah and Kufah schools. The process includes reading, note-taking, and analyzing research materials, with data analysis conducted using comparative content analysis techniques. The findings of this study indicate that while there are differences in the application of Qiyas between the two grammatical schools, both agree that Qiyas is one of the essential foundations of grammatical science.